NILAI-NILAI AJARAN SALAFI DALAM BUKU AJAR BAHASA ARAB AL-ARABIYYAH BAYNA YADAIK (Analisis Semiotik Roland Barthes) - Ubaidillah Ubaidillah (Sunan Kalijaga State Islamic University Yogyakarta, 2014)
This paper aims to find the values of Salafi in Arabic textbook al-Arabiyyah Bayna Yadaik (ABY). These values are analyzed using Barthesian Semiotics. In his views, verbal and non-verbal sign has both connotative and denotative meaning. Therefore this research is critical to find the covert meaning in the textbook in order to get a clear ideological perspective. After reading ABY through Barthesian Semiotic views, this research finds that several Islamic teachings are covertly applied in Salafi groups while others don’t. Those teaching are the obligation to cover the face of women when facing or dealing with men who are not mahram, the ban on praying together in the mosque for women, and prohibition of mixing between men and women who are not mahram in public places. Those are all based on the Quran and Hadits.